Copyright or copyleft: An assessment of farmer-innovators' attitudes towards intellectual property rights - Tambo, Justice A.; Barake, Evelyn; KOUEVI, TEKO AUGUSTIN; MUNTHALI, Grace Timanyechi (My University, 2020)
There is a broad consensus that farmers are not simply recipients of promoted techniques: rather, they are also an important source of agricultural innovations. They invent farm tools and equipment, develop new crop varieties, and add value to externally promoted technologies. When scouting, documenting and promoting such farmer-generated innovations, the thorny issue of intellectual property rights (IPRs) often emerges. Using data from 300 farmer-innovators in Kenya, Malawi and Zambia, this study seeks to contribute to a better understanding of farmers' knowledge of and preferences for IPRs and open-access innovation. Results show that more than half of the innovators have no prior knowledge of IPRs. We found evidence that small-scale farmer-innovators prefer their innovations to be open access rather than protected by IPRs, and this is largely driven by altruistic motives. Some of the reasons cited by the farmers for preferring IPR protection include obtaining financial benefits, recouping the money invested in developing the innovation, wanting to be recognized as the original innovator, and preventing piracy. Consistent with the innovators’ stated reasons, results from a bivariate probit regression show that the commercialization potential of and cost incurred in developing an innovation are among the key correlates of the preference for IPRs.
Keywords: Farmer-generated innovations; Farmer-Innovators; Intellectual property rights; Open Access; Africa